ECPR for cardiac arrest caused by abnormal uterine bleeding and coronary vasospasm: a case report - Sheng, Qiping; Wang, Yingjie; Wu, Zhiyang; Zhao, Xiangyang; Wu, Dawei; Li, Zhi; Guo, Xi (Frontiers in Cardiovascular Medicine, 2024)
IntroductionCardiac arrest during pregnancy is receiving increasing attention. However, there are few reports on cardiac arrest in nonpregnant women caused by abnormal uterine bleeding (AUB). We report a case in which extracorporeal cardiopulmonary resuscitation (ECPR) was used in a patient with cardiac arrest caused by AUB and coronary vasospasm.Patient presentationA 52-year-old female patient presented to the emergency department because of sudden chest pain, with a history of hypertension, coronary heart disease and AUB for more than half a month. At the initial stage of admission, cardiac arrest occurred after the ECG demonstrated ST-segment elevation in leads II, III and a VF. ECPR was started after traditional cardiopulmonary resuscitation, and coronary angiography was performed with the support of extracorporeal membrane oxygenation (ECMO). The left and right coronary arteries were slender and narrow, which was relieved after the injection of 100 µg nitroglycerine through the left coronary artery. After performing a coronary angiogram, the patient was given long-acting nitrates and calcium channel blockers orally, and her chest pain did not reoccur. The patient was weaned from ECMO support after 4 days.ConclusionThis clinical case highlights the challenges that clinicians face in accurately diagnosing and possibly treating AUB and coronary vasospasm-induced acute myocardial infarction because of its rare occurrence and serious adverse events. ECPR can effectively improve the success rate of cardiopulmonary resuscitation.